Development of A Science Module Based on Local Culture of NTT to Enhance Critical Thinking Skills of Prospective Elementary School Teachers - Andriyani Afliyanti Dua Lehan; Hiwa Wonda; Maxsel Koro; Sofia Godeliva Un Lala; Kurniayu Triastuti R.A. Ratu; Treesly Yumiardi Normin Adoe; Gaudensius Koten; Irna Mayangsari Nauk; Dimas Apolos Pada (Jurnal Penelitian Pendidikan IPA, 2024)
The research aims to develop a Science Module based on Local Culture to enhance the Critical Thinking Skills of prospective Elementary School Teachers. This type of research is development research, using the 4D model (Define, Design, Develop, and Disseminate). The subjects of this study were 30 fifth-semester students of the Elementary School Teacher Education Program, who acted as prospective teachers and used the Local Culture-Based Science Module in their coursework as part of a trial of the module's use. The data collection methods employed were questionnaires to gather information on validation, attractiveness, and practicality, as well as tests to assess effectiveness. The data analysis technique used was descriptive quantitative analysis, where total scores and values were calculated and then averaged to be interpreted according to predetermined criteria. The results obtained from the research process showed that the Local Culture-Based Science Module was valid with a validity score of 3.85, attractive with a score of 82.2, practical with a score of 80, and effective with an average final test score of 83.06. In conclusion, the Local Culture-Based Science Module is valid, attractive, practical, and effective for use as a teaching guide for prospective elementary school teachers